MEKANISME CORPORATE GOVERNANCE DALAM PERUSAHAAN YANG MENGALAMI PERMASALAHAN KEUANGAN - Wardhani, Ratna (UI Scholars Hub, 2007)
Corporate Governance mechanisms are believed to have strong impact on the companies ’ performance. The implementation o f Corporate Governance in one company might be different to the implementation o f Corporate Governance in other company due to the characteristics o f the company. This study examines the difference o f Corporate Governance mechanisms in financially distressed firms and non financially distressedfirms. Corporate Governance mechanisms examined in this study are board size, independency o f board, institutional ownership and director ownership. The result o f this study shows that board size has a significant negative impact on the probability o f firm experienced financial distressed after controlling fo r firms asset and leverage. This result is also confirmed by test using lag one year. This study fails to document the evidence o f the relationship o f board independency and ownership structure with the probability o f firm experienced financial distressed.